Fractal-view and convergence of fractional order cauchy reaction-diffusion equations using semi-analytical technique - H.M. Younas; Kousar Yousaf; Imran Siddique; Shaukat Iqbal (Partial Differential Equations in Applied Mathematics)
This article solves time-fractional order Cauchy reaction-diffusion equations in approximation using the Optimal Homotopy Asymptotic Method (OHAM).The exact solutions and approximate third-order results achieved using OHAM are compared. It has been noted that for partial time order Cauchy equations for reaction-diffusion, OHAM findings exhibit a substantial convergence rate. Plotting the outcomes of the solutions and tabulating the relative errors are done. In order to find the mentioned solutions Mathematica has been used.